Don't worry and measure FFR. Issue 1 (2nd August 2018) - Ahn, Jung‐Min; Park, Seung‐Jung
KEY POINTS: FFR‐guided PCI was associated with better clinical outcomes regarding the reduction of myocardial infarction and major adverse cardiac events. The clinical benefit of FFR‐guided PCI was achieved with less stents and procedural cost, without additional effects on procedural time and contrast volume. Physicians should measure FFR of target stenosis prior to PCI if there is no objective evidence of myocardial ischemia.